Development of Decision-Making Tool for Family Planning Application: Feasibility Test According to Material Experts - Nurcahyani, Lia; Widiyastuti, Dyah; Hasan, Faizul; Cahyati, Yanti; Badriah, Siti (Open Access Macedonian Journal of Medical Sciences, 2022)
The high unmet need affected the high maternal mortality rate in Indonesia. One of the factors causing unmet needs is unoptimal family planning counseling. The tool used for family planning counseling in Indonesia is the decision-making tool for family planning flipchart. However, the use of the flipchart is not optimal because it has various limitations such as being less practical. Researchers have innovated in making decision-making tools for a family planning application. This study aims to develop the decision-making tool for a family planning application by conducting a feasibility test by material experts. This was a research and development study design. The research subjects were six midwives as material experts. The research instrument includes the decision-making tool for a family planning application, as well as a questionnaire. Data analysis includes descriptive univariable analysis. The results of the feasibility test for the decision-making tool for family planning application according to material experts obtained a value of 81.3%, which is categorized as very suitable for use as a family planning counseling medium. Further researchers are expected to develop a second-level application by conducting a trial limited-scale, wide-scale trials, and level 3 testing with experimental designs using a control group.